Housing management practices followed by Buffalo owners in Purandar Tehsil of Pune district (Indian Journal of Animal Production and Management, 2024)
The present study on socio economic status and housing management practices followed by buffalo  owners was undertaken in Purandar tehsil, of Pune, district Maharashtra state. For this study 150 buffalo  owners were chosen randomly as respondents from 15 selected villages. Data was collected through  pretested questionnaire. The owners were distributed in three groups viz., group-I, group-II and group-III  on the basis of buffaloes possessed by them as up to 4, 5 to 8 and more than 9 buffaloes, respectively.  Majority (50.00%) of buffalo owners were between age of 31-50 years, whereas, 14.66 % farmers were  educated up to graduation level. Majority (88.33%) of buffalo owners had provided shed facility to their  buffaloes. Permanent buffalo shed was provided by 73.33 % farmers. About 32.00 % farmers were providing  thatched roofing, 50.66 % farmers were providing G.I. sheets and very few (17.33%) farmers were using  asbestos for roofing. Majority (74.00%) farmers provided optimum size manger. There was positive and  significant (P
Keywords: Buffaloes; Housing; Socio-economic